2016
DOI: 10.1111/cge.12797
|View full text |Cite
|
Sign up to set email alerts
|

Whole gene duplication of SCN2A and SCN3A is associated with neonatal seizures and a normal intellectual development

Abstract: Duplications at 2q24.3 encompassing the voltage-gated sodium channel gene cluster are associated with early onset epilepsy. All cases described in the literature have presented in addition with different degrees of intellectual disability, and have involved neighbouring genes in addition to the sodium channel gene cluster. Here, we report eight new cases with overlapping duplications at 2q24 ranging from 0.05 to 7.63 Mb in size. Taken together with the previously reported cases, our study suggests that having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…Moreover, in the SCN CNV cohort, we observed that patients with duplications presented with significantly earlier seizure onset and responded better to SCBs compared to patients with deletions. This early seizure onset is likely caused by duplication of the SCN2A/SCN3A genes, which are the earliest SCN s expressed during development, resulting in GoF effects due to SCN2A/SCN3A protein overexpression …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the SCN CNV cohort, we observed that patients with duplications presented with significantly earlier seizure onset and responded better to SCBs compared to patients with deletions. This early seizure onset is likely caused by duplication of the SCN2A/SCN3A genes, which are the earliest SCN s expressed during development, resulting in GoF effects due to SCN2A/SCN3A protein overexpression …”
Section: Discussionmentioning
confidence: 99%
“…This early seizure onset is likely caused by duplication of the SCN2A/SCN3A genes, which are the earliest SCNs expressed during development, resulting in GoF effects due to SCN2A/SCN3A protein overexpression. 41…”
Section: Discussionmentioning
confidence: 99%
“…Yoshitomi et al (127) reported 3 patients manifesting focal seizures and infantile spasms having microduplication mutation on the 2q24.3 chromosomal loci. Eight additional duplications were reported by Thuresson et al (128). The region duplicated was overlapped and the spanned range approximately between 0.05 and 7.63 Mb in size.…”
Section: Deletion Regionsmentioning
confidence: 90%
“…Table 1 summarizes the patients reported to have EIEE due to either heterozygous or de novo mutations within the SCN2A gene. 7,12…”
Section: Discussionmentioning
confidence: 99%